Superior health-related physical fitness and well-being in 12–15-year-old Danish adolescents who are active in organized leisure-time sports – a cross-sectional study - Christina Birch Meiner; Caroline Eckert; Charlotte Sandager Aggestrup; Kristina Pfeffer; Giampiero Tarantino; Camilla Prisak; Chiara Cimenti; Cecilie Thøgersen-Ntoumani; Nikos Ntoumanis; Peter Krustrup; Malte Nejst Larsen (PLoS ONE, 2025)
Background Global reports indicate that less than 20% of 11–17-year-olds meet physical activity recommendations, and while organized sports participation increases the likelihood of meeting these guidelines, no other studies were found that examined the impact on well-being and physical fitness outcomes among Danish adolescents based on participation in leisure time sports. Methods The study employed a cross-sectional design, assessing cardiorespiratory fitness, fat percentage, and well-being, as well as several other health and fitness outcomes among 1,333 Danish adolescents (50% girls). Differences between participants in organized sports and non-participants, as well as between participants in different sport categories were assessed through ANCOVA analysis. Results Girls and boys participating in organized sports, ran longer (p<0.05) in the Yo-Yo Intermittent Recovery level1 Children's test (IR1C) (G: d = 0.72 [0.54; 0.89]; B: d = 0.70 [0.50; 0.89]) and had lower (p<0.05) fat percentages than non-participants (G: d = 0.42 [0.25; 0.59]; B: d = 0.33 [0.14; 0.51]). Organized sport participants had higher (p < 0.05) well-being than non-participants in all KIDSCREEN-27 sub-scales apart from social support and peers. Girls in individual sports had lower (p<0.05) well-being than girls in other sports in all sub-scales apart from parent relations and autonomy. Multisport participation for both sexes, as well as participation in soccer for boys, was associated with a greater distance covered in the Yo-Yo IR1C (p < 0.05). A significant drop out of sports from the previous to the current year was found among girls, but not among boys. Conclusion Participation in organized leisure-time sports is linked to better health, fitness, and well-being, especially for girls, who show greater disparities with non-participants. Participation in team sports is linked to higher well-being compared to individual sports in girls, but not in boys. High dropout rates among adolescent girls call for targeted strategies to sustain their participation and derived benefits.